2017
DOI: 10.1002/dc.23688
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic involvement by metastasizing neoplasms as determined by endoscopic ultrasound‐guided fine needle aspiration: A clinicopathologic characterization

Abstract: Metastases to the pancreas can be diagnosed via EUS-FNA, with enough specimen to conduct immunohistochemical studies if necessary to delineate origin. The determination of metastatic disease to the pancreas alters management and prognosis of the patient. Diagn. Cytopathol. 2017;45:418-425. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
(123 reference statements)
0
15
0
1
Order By: Relevance
“…[3][4][5] In contrast to primary lesions, metastases to the pancreas are rarely aspirated and only 0.73%-4.2% of the total pancreatic FNAs are performed on the grounds of a metastasis. 1,[6][7][8][9] Aspirated metastases most often present as solitary lesions located in the pancreatic head and surrounded by well-defined borders. 1,8,[10][11][12][13] Most patients diagnosed with such lesions have a prior history of malignancy; however, metastases to the pancreas might appear long after the initial diagnosis, especially in the case of renal cell carcinoma (RCC).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] In contrast to primary lesions, metastases to the pancreas are rarely aspirated and only 0.73%-4.2% of the total pancreatic FNAs are performed on the grounds of a metastasis. 1,[6][7][8][9] Aspirated metastases most often present as solitary lesions located in the pancreatic head and surrounded by well-defined borders. 1,8,[10][11][12][13] Most patients diagnosed with such lesions have a prior history of malignancy; however, metastases to the pancreas might appear long after the initial diagnosis, especially in the case of renal cell carcinoma (RCC).…”
Section: Introductionmentioning
confidence: 99%
“…14 RCC has been reported to be the most common origin of pancreatic metastases diagnosed with FNA; lung, colon, breast carcinomas and melanoma are also enlisted as relatively prevalent primaries. 1,6,[8][9][10][11]14,15 An accurate distinction between a metastatic and a primary neoplasm in the pancreas is imperative due to the difference in their therapeutic strategy and prognosis. 13,15 Metastases might mimic primary neoplasms in clinical, radiological and cytomorphological settings thus their differential diagnosis can be a challenging task for the cytopathologist, especially in the absence of clinical history.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En nuestro caso, el diagnóstico preoperatorio fue realizado con PAF-USE, similar a lo descrito en 8/24 casos reportados, resultando ser una técnica precisa para el diagnóstico, que permite evitar la biopsia abierta 5,7 . USE se reconoce como el examen más sensible (94-100%) para detectar lesiones tumorales pancreáticas, junto con su capacidad de distinguir lesiones primarias de metastásicas y la realización de punción por aguja fina 8,9 . Entre las características endosonográficas de las metástasis pancreáticas se incluye la hipoecogenicidad, heterogeneidad y bordes variablemente definidos 10 .…”
Section: Discussionunclassified
“…1 Over the past few years, several studies have confirmed the diagnostic utility of FNAB in cancer, and therefore, it is now widely used in clinical practice. [2][3][4][5][6][7][8][9][10][11] Owing to innovative developments in FNA technology, we can now collect more cells to prepare cell blocks (CB) that can be used for cell smears and immunohistochemistry (IHC) staining analysis, which compensates for some of the shortcomings of simple smears in organisational structure and cell morphology. IHC analysis represents an important technique to improve the accuracy of FNAB diagnoses.…”
Section: Introductionmentioning
confidence: 99%